Enhancing soil aggregate stability in mixed plantation of Eucalyptus urophylla and Acacia mangium - Yeming You; Danyang Hou; Hailun Ma; Yi Wang; Yijia Huang; Zhouyu Luo; Haimei Huang; Lu Zheng; Xueman Huang (Applied Soil Ecology, 2026)

Investigation of the hydrodynamic characteristics of the underwater propulsion pump blade based on a bionic strategy - Miao Jin; Haoran Liu; Guoyong Jin; Fangming Zhou; Yeming Lu; Xiaofang Wang (Ocean Engineering, 2025)

Longitudinal landscape of immune reconstitution after acute SARS-CoV-2 infection at single-cell resolution - Lili Ren; Yiwei Liu; Yeming Wang; Chao Wu; Li Guo; Lan Chen; Xinming Wang; Yan Xiao; Lixue Huang; Jingchuan Zhong; Jiacheng Yao; Lu Liu; et al. (Science Bulletin, 2025)

Flow-heat coupling analysis of the 1/4 symmetrical CAP1400 nuclear island loop based on the source term approach - Yeming Lu; Zhenyang Guo; Meina Zhang; Meina Zhang; Xiaomo Jiang; Xiaofang Wang (Annals of Nuclear Energy, 2025)

Multi-objective evolutionary neural architecture search for network intrusion detection - Qiuzhen Lin; Zhihao Liu; Yeming Yang; Ka-Chun Wong; Yahui Lu; Jianqiang Li (Swarm and Evolutionary Computation, 2024)

Underwater propeller turbine blade redesign based on developed inverse design method for energy performance improvement and cavitation suppression - Yeming Lu; Zhenyang Guo; Zeyu Zheng; Wei Wang; Hui Wang; Fangming Zhou; Xiaofang Wang (Ocean Engineering, 2023)

Study of the Operating Characteristics for the High-Speed Water Jet Pump Installed on the Underwater Vehicle with Different Cruising Speeds - Yeming Lu; Haoran Liu; Xiaofang Wang; Hui Wang (Journal of Marine Science and Engineering, 2021)
Due to the higher propulsive efficiency, lesser vibration, and better maneuverability, the water jet pump is widely applied to high-speed underwater vehicles. By taking a newly developed water jet pump system as the object, the corresponding underwater vehicle’s operating characteristics affected by different cruising speeds (15.43, 30.86, and 52.47 m/s) were investigated. The steady results reply that the cruising speed increase will result in the decline of the overall performances comprised of the head, the efficiency, the thrust, and the power. While, by using different analyzing methods, the unsteady results are listed as follows: (1) The energy loss theory denotes that the increasing cruising speed promoted the kinetic energy diffusion from the Reynolds stress and viscous stress and depress the turbulent kinetic energy production and the viscous dissipation. (2) The statistical PLS method reveals that the tip load effect on the leakage flow becomes weaker when the cruising speed becomes larger, while the effect from the scraping pressure has a completely opposite trend. (3) Further unsteady analysis implies that the increasing cruising speed makes the pressure pulsation larger and makes the radial force, the axial force, and the cloudy cavity size smaller.